Integrated Approach to Wastewater Use in Agriculture: A Pilot Study in Rajshahi City Corporation Area - Chowdhury, A; Alam, MZ; Masum, AA (Journal of Environmental Science and Natural Resources, 2015)
Demand for water is increasing in the world parallel to increase in population and industrialization. In many developing countries, wastewater is the only source of water for irrigation during dry periods. Besides, wastewater is high in nutrient content which reduces the use of chemical fertilizers for crop cultivation. After a certain period, it will be unable to irrigate with ground water because of its limited quantities and contamination. To overcome this difficulties waste water may be a suitable source to meet the irrigation demand if properly managed and utilized in convenient way. In this study, wastewater samples were collected from four places of Rajshahi City Corporation (RCC) for determining water quality parameters. Analysis of these impurities were performed with strict quality control and quality assurance using the internationally accepted analytical chemical methods for the determination of their harmful effects on crops and found that most of the parameters exceed the permissible limits. The major problem in using wastewater in agriculture in the project area is the high level of faecal contamination. Thus, efforts are geared toward finding ways of utilizing the previously unused sources of water and/or recycling wastewater. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22061 J. Environ. Sci. & Natural Resources, 6(1): 167-171 2013